THE IMPACT OF WORK-RELATED FACTORS ON JOB PERFORMANCE AMONG HEALTHCARE TECHNICIANS IN SAUDI ARABIA - Ahlam Hameed Bathi Aldhafeeri, Afaf Amer Dh Aldhafeeri, Fatimah Amer Dhahawi Aldhafeeri, Fatimah Haif Hamdan Aldhafeeri, Hameed Hulayyil Nazal Alanazi, Dhari Khalif Sayil Aldhafeeri, (Chelonian Research Foundation, 2022)
Objective: This study aimed to investigate the impact of work-related factors on job performance among healthcare technicians in Saudi Arabia. Methods: A cross-sectional survey was conducted among 500 healthcare technicians (250 nursing technicians and 250 anesthesia technicians) working in various hospitals across Saudi Arabia. Participants completed a self-administered questionnaire assessing work-related factors (workload, job stress, job satisfaction, and perceived organizational support) and job performance. Multiple linear regression analysis was used to examine the predictors of job performance. Results: The response rate was 94% (n=470). The mean age of participants was 32.5 years (SD=6.7), and 70.2% were female. The mean scores for workload, job stress, job satisfaction, perceived organizational support, and job performance were 3.8 (SD=0.8), 3.6 (SD=0.9), 3.4 (SD=1.0), 3.3 (SD=1.1), and 3.7 (SD=0.7), respectively. Multiple linear regression analysis showed that workload (β=-0.25, p<0.001), job stress (β=-0.18, p<0.01), job satisfaction (β=0.32, p<0.001), and perceived organizational support (β=0.27, p<0.001) were significant predictors of job performance, after controlling for demographic and work-related characteristics. Conclusion: Work-related factors, including workload, job stress, job satisfaction, and perceived organizational support, significantly influenced job performance among healthcare technicians in Saudi Arabia. Healthcare organizations should implement strategies to optimize these factors and enhance job performance in this important workforce. Keywords: healthcare technicians, job performance, workload, job stress, job satisfaction, perceived organizational support, Saudi Arabia